Ablation Behaviour and Microstructure of Carbon/Carbon and Hybrid Carbon/Carbon Composites Based on Plasma Torch Heating. Issue 4 (July 2017) - Ma, Li; He, Lu Jv; Mo, Cai Song; Zhang, Li Bin; Pan, Mao Sen; Huang, Yang F feng
The ablation properties and morphologies of two kinds of fine Fine-woven pierced composites materials, carbon/carbon (C/C) and hybrid C/C with tungsten (W) filaments in z directional carbon fibre bundles, were investigated. A plasma torch was used to explore the ablative characteristics in terms of linear/bulk ablation rate and microscopic pattern of ablation. Surface and in-depth temperatures during ablation were measured by using optical pyrometers and thermocouples. The experimental results showed that the C/C composite presented the best ablation resistance performance, followed by the hybrid C/C composite, while that of graphite was the worst. It was found that the thermo-mechanical ablation resistance of carbon matrix is equal to that of carbon fibres. The existence of WC not only had a faster intrinsic ablation velocity, but also accelerated the ablation velocity of the carbon fibres and carbon matrix, and significantly improved the ablation velocity of the carbon fibres.